2005
DOI: 10.1111/j.1532-849x.2005.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Accuracy of 7 Die Materials

Abstract: Type IV resin-impregnated dental stone and copper-plated dies were more dimensionally accurate than the other die materials tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 14 publications
3
40
0
4
Order By: Relevance
“…However, in the case of research on the repeatability of full arch model scans, it was difficult to determine errors in the abutments that are most important for prosthesis fabrication. Therefore, in this study, we selected an impression body for each abutment tooth 1,4,7,16,17) . Previous studies showed that the repeatability of the stone model scanning was higher, in general, than that of impression scanning 3,4) .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of research on the repeatability of full arch model scans, it was difficult to determine errors in the abutments that are most important for prosthesis fabrication. Therefore, in this study, we selected an impression body for each abutment tooth 1,4,7,16,17) . Previous studies showed that the repeatability of the stone model scanning was higher, in general, than that of impression scanning 3,4) .…”
Section: Discussionmentioning
confidence: 99%
“…Analoge gebitsmodellen worden verkregen door conventionele analoge afdrukken uit te gieten met een slijtvast en dimensionaal stabiel steengips (type IV) of met een kunstharsversterkt gips (Kenyon et al, 2005). De gebitsmodellen worden zo vervaardigd dat de (geprepareerde) gebitselementen individueel uitneembaar en reponeerbaar zijn om tandtechnische handelingen mogelijk te maken.…”
Section: Analoogunclassified
“…The use of dimensionally accurate materials such as type IV resin-impregnated and copper-plated dies should result in the development of a crown margin that lies in more intimate contact with the finish line of the tooth preparation, given that the dimensional changes of the wax pattern, alloy and investment are carefully matched. 3 Type IV and V gypsum dies recorded the greatest variation in dimensions than the other die materials examined. The minimal setting expansion of conventional type IV and V dental stone should result in the fabrication of satisfactory crown margins and provide enough space between the casting and the tooth to allow complete seating without binding and space for a film of cement.…”
mentioning
confidence: 99%
“…Some investigators have found electroplated dies to be more dimensionally accurate than stone dies while others have demonstrated otherwise. 3 The awareness of infectious diseases and the recognition of the potential for transmission of infection during dental procedures have increased concern and attention to infection control in dental practice. 4 Disinfection provides a method of preventing the transmission of these microorganisms from the patient to dental personnel who handle the impression or stone cast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation